محمد بخش نوروز کی سرائیکی کافی: ایک مطالعہ (Al-Aasar, 2025)
Kafi is one of the oldest and most popular literary genres of the Saraiki language. Many Saraiki Sufi poets used it as a medium of expression to convey the secrets and subtleties of mysticism. In Shah Latif’s Saraiki poetry, a form similar to wai can be found, which, in terms of structure, bears a strong resemblance to the kafi. However, the formal journey of the Saraiki kafi is considered to have begun with Hazrat Sachal Sarmast. After the era of Sachal, the great poet Hazrat Khawaja Ghulam Farid elevated the Saraiki kafi to unparalleled heights. Among his contemporaries, Muhammad Bakhsh Nawroz, a poet from Mubarakpur—a well-known area in Ahmedpur East Tehsil of the Bahawalpur state—holds special significance. Muhammad Bakhsh Nawroz diverged from the centuries-old mystical tradition of Saraiki kafi and explored new paths of expression, establishing himself as a poet who brought innovation to the genre. The present research paper is an attempt to explore the life of Muhammad Bakhsh Nawroz and analyze the themes of his poetry.